ISLAM IN DIGITAL AGE: THE APPLICATION OF MAQĀSID AS-SYARI’AH ON DIGITAL ZAKAT - umi cholifah (Institut Agama Islam Ma'arif NU (IAIMNU) Metro Lampung, 2019)
The digital era is utilized by many institutions in facilitating consumers to transact. One of them is transaction for zakat. However, zakat is a worship commanded by Allah. Then, the use of digitizing zakat should also be submissive and obedient to the rules established by Allah. On the other hand, in the Islamic rules there is something very important which can be used to approach contemporary issues comprehensively. It is also the objectives of Islamic law contained in each rule. It is namely maqāsid as-syari’ah. Through descriptive normative study, this paper will offer concepts of maqāsid as-syari’ah which can be applied in zakat on digital finance. Finally, this study aims to explore the concepts of legality and strengthening strategies for zakat on digital finance based on maqāsid as-syari’ah. The results of this study is some verses that have the basic word zakat are in the first reference to explore the legal content of zakat on digital finance. From the legal basis, it appears that in legal concept, the provisions that exist in zakat on digital finance must be in accordance with the rules of zakat in Islam. As for steps to strengthen zakat in terms of two aspects, there are the scope of legal objectives and the subject. Abstrak Era digital dimanfaatkan oleh banyak lembaga dalam memfasilitasi konsumen untuk bertransaksi. Salah satunya adalah transaksi zakat. Namun, zakat merupakan ibadah yang diperintahkan oleh Allah. Oleh karenaitu, penggunaan digitalisasi zakat juga harus tunduk dan patuh pada aturan yang ditetapkan oleh Allah. Di sisi lain, di dalam aturan Islam terdapat sesuatu yang sangat penting yang biasa digunakan untuk mendekati masalah kontemporer secara komprehensif. Hal ini juga merupakan suatu tujuan hukum Islam yang terkandung dalam setiap aturan, yang disebut dengan maqāsid as-syari'ah. Melalui studi normative deskriptif, tulisan ini menawarkan konsep maqāsid as-syari'ah yang dapat diterapkan dalam zakat pada keuangan digital. Akhirnya, penelitian ini bertujuan untuk mengeksplorasi konsep legalitas dan memperkuat strategi zakat pada keuangan digital berdasarkan maqāsid as-syari'ah. Adapun hasil dari penelitian ini adalah beberapa ayat yang memiliki kata dasar zakat ada dalam referensi pertama untuk mengeksplorasi konten hukum zakat pada keuangan digital. Dari dasar hukum, tampak bahwa dalam konsep hukum, ketentuan yang ada dalam zakat pada keuangan digital harus sesuai dengan aturan zakat dalam Islam. Adapun langkah-langkah untuk memperkuat zakat dalam dua aspek yaitu ruang lingkup tujuan hukum objek dan subjek.